DEVELOPMENT OF VIDEO LEARNING MEDIA ON EXCRETION SYSTEM MATERIAL FOR CLASS XI SMA NEGERI 18 MEDAN T.A. 2023/2024 - Sipayung, Yariski; Sipahutar, Herbert (Universitas Negeri Medan, 2025)
This research aims to develop and test the feasibility of video learning media and test its influence on student learning outcomes in the distribution stage on human excretory system material. Learning media is developed based on the 4D development model which consists of four stages, namely definition, design, development and distribution. Media is validated by media experts and learning experts. Responses from biology teachers and students of class XI MIA 1 SMA Negeri 18 Medan. Research data was obtained through validation instruments, questionnaires and cognitive tests. Data was analyzed qualitatively and quantitatively. The research results showed that the video learning media developed was considered very feasible by material experts (97,94%), media experts (93,66%). Video learning media was rated as very appropriate and very good by biology teachers (96.94%) and students (82.91%). From the t test, the calculated t value = 13,491 and t table = 1.69092 which shows that t calculated > t table. These data show that cognitive test results have increased significantly after using the video learning media developed.